Factors affecting value co-creation effectiveness in digital library service quality - Moses, Golooba; Ahlan, Abdul Rahman (IIUM Press, 2017)
Academic libraries just like other contemporary organisations are increasingly depending on the Value Co-creation Business Strategy as the main locus of service creation and service delivery since it offers an effective Model for re-organization to reduce costs, optimizing resource usage and for enhancing customer service performance. Overall, the rapid advancements in digital technologies have made the value cocreation model as the most convenient and cost-effective business strategy for academic libraries as it allows library users to co-create their own experiences; and also enables academic libraries to reduce operational costs by way of investing only in resources that target performance gaps, thus avoiding un-necessary duplicated investments. Given the growing importance of the value co-creation Business Strategy, there is an increasing need to understand the various factors which may affect the overall value co-creation effectiveness. Unfortunately there is still a dearth of research focusing the notion of value co-creation in particular, and on the factors which may affect value co-creation effectiveness in general. Moreover, related studies are still largely fragmented and researchers are still divergent in the way they conceptualize the key variables. To bridge this gap, the researchers seek to propose a holistic model, which integrates the various strands of research related to value co-creation effectiveness, particularly in the context of digital library service quality. Accordingly, the researchers use the lens of the Information Systems Success Model (ISSM) to integrate the various strands of related literature; and also draw insights from two dominant theories; the Service Dominant Logic (SDL) and the Social Cognitive Theory (SCT) to extend this particular knowledge domain. In carrying out the empirical study, the researchers follow a quantitative research strategy. Data is collected from postgraduate students of selected Malaysian public universities using a survey instrument. This data is later analysed using both Exploratory Factory Analysis (EFA) and Confirmatory Factor Analysis (CFA); specifically using the Statistical Package for the Social Science (SPSS) and Analysis of Moment Structures (AMOS) statistical tools respectively.